P PENGARUH PEMBERIAN MADU LEBAH TERHADAP TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI - Natar Fitri Napitupulu (CHMK NURSING SCIENTIFIC JOURNAL, 2020)
Abstract Hypertension is defined as persistent blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. One of the ingredients of honey to reduce blood pressure is flavonoids. The design used in this study was "Quasi experimental pre-post test" by involving the control group and intervention group. The research subjects were Stage 1 hypertension sufferers and as many as 50 respondents using the convenience sampling method, in which 25 respondents were the experimental group and 25 were the control group respondents. Honey is given 20 cc for 7 days. The results of statistical tests in the experimental group and the control group using the dipendent sample t-test results from the intervention p-value and the control group with the Sig. (2-tailed) of 0,000 <0,05. Comparison of the following MAP in the experimental group and the control group using indipendent sample t-test with the Sig. (2-tailed) of 0,000 <0,05. The conclusion is the effect of giving honey bee to the reduction of blood pressure in elderly people with hypertension. Keywords: Honey Bee, Blood Pressure, Elderly, Hyperte